Literature Study of the Influence of Project-Based Learning (PjBL) Models on Creative Thinking Ability of Students - Subeli, Rizal; Sapriya, Sapriya (International Conference on Elementary Education, 2020)
The purpose of this literature study is to find out whether creative thinking ability can be influenced by the Project Based Learning (PjBL) model, given that this model is one of the leading models in increasing creative thinking abilities. This model can also encourage the ability of students to solve problems, ideas and new products. In everyday life, a person cannot be separated from the activities of thinking. One of the activities of thinking needed in life is creative thinking. The development of the ability to think creatively can be done through school education, which is one of them in the process of learning and learning. The method used is a literature study method of several references that discuss the effect of this model on students' creative thinking abilities, the results of the literature study found that the Project Based Learning (PjBL) model has an influence on increasing the ability to think creatively in various subjects and various Elementary school, Junior and Senior High school